PEROLEHAN MINERAL BESI DARI RESIDU BAUKSIT INDONESIA - Sariman; Rochani, Siti; Saleh, Nuryadi; Wijayanti, Retno; Dianawati, Erika Arum (Indonesian Mining Journal, 2024)
Bauxite residue, a solid waste discharged during alumina extraction, is a hazardous material. Its disposal leads to a serious environmental issue although it contains valuable matter such as titanium, silica, rare earth elements, and high iron content (20-60%). This work aims to improve the recovery of iron content within the bauxite residue using three methods, namely direct magnetic separation, roasting followed by magnetic separation, and reduction followed by magnetic separation. Coal as a reductant and Na2CO3 and Na2SO3 as fluxes were used in the reduction process. The result of the study reveals that the direct magnetic separation produces iron concentrate with the Fe content of 53.69% and a recovery of 26.72%, while the roasting process at 900˚C and magnetic separation produces a concentrate of 54.57% Fe with a recovery of 37.33%. The best method was by reduction and magnetic separation process using 4% of Na2CO3  producing iron concentrates with a content of 63.53% Fe and recovery of 74.73%.